DAMPAK PENGEMBANGAN DESTINASI PARIWISATA TERHADAP ALIH FUNGSI LAHAN SAWAH STUDI KASUS DI DESA PETITENGET KUTA UTARA BADUNG - I Made Trisna Semara; I Putu David Adi Saputra (Institut Pariwisata dan Bisnis Internasional, 2015)
The purpose of this research is to know the impact of tourism development toward rice field function alteration. It is located at Petitinget village, north Kuta, Badung. This research is used qualitative method. It is used to get the data or descriptive information about rice field function alteration. Descriptive-qualitative is used to analyze the data.According to the result of this research, there is a significant influence toward rice field function alteration and tourism development at Petitenget area. It impacts to the life of society and makes a negative impact to social, economic, and environment to the tourism area at Petitenget.